2016
DOI: 10.1063/1.4958323
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic effects on β-amyloid (16-22) peptide aggregation

Abstract: Computer simulations based on simplified representations are routinely used to explore the early steps of amyloid aggregation. However, when protein models with implicit solvent are employed, these simulations miss the effect of solvent induced correlations on the aggregation kinetics and lifetimes of metastable states. In this work, we apply the multi-scale Lattice Boltzmann Molecular Dynamics technique (LBMD) to investigate the initial aggregation phases of the amyloid Aβ16-22 peptide. LBMD includes naturall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 92 publications
1
54
0
Order By: Relevance
“…Lateral branching is described theoretically by a second nucleation mechanism [46], but while observed experimentally for some proteins [47,48], it has never been reported from molecular simulations. In a recent work [49] reporting on the effect of hydrodynamics on the aggregation process of Aβ 16−22 peptides in systems of different sizes, we have demonstrated that hydrodynamic interactions not only speed up the aggregation with respect to standard Langevin dynamics, but also enhance the fluctuations of the sizes of the formed clusters along the aggregation. It was speculated that the peptides aggregates act on the solution as active particles [9], and the change of their conformations and sizes generate coherent fluid flows that further favour the fusion of small entities in larger complexes.…”
Section: (B) Amyloidsmentioning
confidence: 81%
“…Lateral branching is described theoretically by a second nucleation mechanism [46], but while observed experimentally for some proteins [47,48], it has never been reported from molecular simulations. In a recent work [49] reporting on the effect of hydrodynamics on the aggregation process of Aβ 16−22 peptides in systems of different sizes, we have demonstrated that hydrodynamic interactions not only speed up the aggregation with respect to standard Langevin dynamics, but also enhance the fluctuations of the sizes of the formed clusters along the aggregation. It was speculated that the peptides aggregates act on the solution as active particles [9], and the change of their conformations and sizes generate coherent fluid flows that further favour the fusion of small entities in larger complexes.…”
Section: (B) Amyloidsmentioning
confidence: 81%
“…In a study for the Aβ16−22 peptide, it was defined by a flexible OPEP model and the initial aggregation phase study was done using multi-scale Lattice Boltzmann molecular dynamics. The hydrodynamic interaction effect was studied and found to enhance the aggregation process [106]. In another work, the OPEP model has been implied to study the amyloid fibril formation along with interactive simulations for peptide folding and response to mechanical stress caused by the surrounding fluid by catch bond proteins [105].…”
Section: Opep (Optimized Potential For Efficient Structure Prediction)mentioning
confidence: 99%
“…It is based upon the kinetic description of the solvent explained by the fluid dynamics under varied conditions. LB-based hydrodynamics in combination with the OPEP coarse-grained model for proteins have been reported to study the protein relaxation and aggregation processes [106,159,160].…”
Section: Multiscale Simulations and Coarse-grained Modelsmentioning
confidence: 99%
“…Amyoid aggregation represents an examplar instance of hydrodynamic forces impacting the formation of molecular aggregates. By studying a system of unprecedented size, LBPD simulations were able to explore a branched disordered fibril-like structure that had never been described by computer simulations before [97]. The results show that hydrodynamics forces also steer the growth of the leading largest cluster and impact the aggregation kinetics and the fluctuations of the oligomer sizes, by favouring the fusion and exchange dynamics of oligomers between aggregates.…”
Section: Protein Diffusion and Amyloid Aggregationmentioning
confidence: 99%